Energy Metabolism and Metformin: Effects on Ischemia-Reperfusion Injury in Kidney Transplantation - Denise V. Nemeth; Leonardo Iannelli; Elena Gangitano; Vito D’Andrea; Maria Irene Bellini (Biomedicines, 2024)
Metformin (MTF) is the only biguanide included in the World Health Organization’s list of essential medicines; representing a widespread drug in the management of diabetes mellitus. With its accessibility and affordability being one of its biggest assets, it has become the target of interest for many trying to find alternative treatments for varied pathologies. Over time, an increasing body of evidence has shown additional roles of MTF, with unexpected interactions of benefit in other diseases. Metformin (MTF) holds significant promise in mitigating ischemia-reperfusion injury (IRI), particularly in the realm of organ transplantation. As acceptance criteria for organ transplants expand, IRI during the preservation phase remain a major concern within the transplant community, prompting a keen interest in MTF’s effects. Emerging evidence suggests that administering MTF during reperfusion may activate the reperfusion injury salvage kinase (RISK) pathway. This pathway is pivotal in alleviating IRI in transplant recipients, potentially leading to improved outcomes such as reduced rates of organ rejection. This review aims to contextualize MTF historically, explore its current uses, pharmacokinetics, and pharmacodynamics, and link these aspects to the pathophysiology of IRI to illuminate its potential future role in transplantation. A comprehensive survey of the current literature highlights MTF’s potential to recondition and protect against IRI by attenuating free radical damage, activating AMP-activated protein kinase to preserve cellular energy and promote repair, as well as directly reducing inflammation and enhancing microcirculation.